Pengaruh Penggunaan Media Pembelajaran Interaktif Animasi Terhadap Motivasi Belajar Siswa Pada Mata Pelajaran Ipa - Hasriani, Hasriani; Ahmad, Ahmad; Saputra, Erwin Eka (Universitas Sulawesi Tenggara, 2024)
This research is an experimental quantitative research. The sampling technique in this study used cluster random sampling technique with a sample in this study of 60 students in grade IV of SDN 10 Mowila. The data collection technique in this study used a questionnaire and documentation. The data analysis technique in this study was the paired sample t-test and independent sample t-test. Based on the hypothesis testing using the paired sample t-test, it shows that; (1) there is a difference in the initial and final conditions of the control class with the results of the calculation of the significance value of 0.0000.05, then Ho is rejected, meaning that there is a significant difference, students' learning motivation after being given treatment is more effective compared to before being given treatment using conventional media, (2) there is a difference in the initial and final conditions of the experimental class with the results of the calculation of the significance value of 0.0000.05, then Ho is rejected, meaning that there is a significant difference, students' learning motivation after being given treatment is more effective compared to before being given treatment using animated video media, (3) there is an effect of the use of learning media on the Learning Motivation of class IV students of SDN 10 Mowila in the 2023/2024 academic year with the results of the calculation of the independent sample t-test showing that the significance value of 0.0000.05, then Ho is rejected, meaning that there is an effect of the use of learning media on the Learning Motivation of class IV students of SDN 10 Mowila in the 2023/2024 academic year.